Measurement of ground borne vibrations for foundation design and vibration isolation of a high-precision instrument. (November 2016) - Ulgen, D.; Ertugrul, O.L.; Ozkan, M.Y.
Highlights: Ground borne vibrations generated by heavy vehicles were measured. Design considerations for foundation of a high-precision instrument were evaluated. Constructing a pile foundation system was recommended. Measurements showed that springs with wire mesh might be a feasible application. Surge frequencies of helical coil springs should be taken into consideration. Abstract: This study focuses on the foundation design and vibration isolation of a high-precision instrument subjected to ground-borne vibrations. The allowable vibration level for the proper operation of the sensitive equipment was 50 μg in a frequency range of 1–300 Hz. Prior to foundation design, first, an extensive field survey including geological and geophysical tests were performed in situ to obtain the static and dynamic physical properties of the soils. Next, vibration levels at various locations in the vicinity of moving vibration sources at the site were measured by accelerometers in one third octave frequency range from 1 Hz to 1000 Hz. Background vibration levels at the site were also measured while all of the vibration sources were inactive. Based on the measurements, a special foundation system was designed to reduce the vibration levels at the base of the precision instrument to allowable vibration limits while the vibration sources were active. Consequently, measurements were performed on the actual true scale foundation structure constructed at the site to assess the vibration isolation performance of specially designed structure. The actual vibration levels on top of the inertia mass show good agreement with the predicted values.